(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The President of the Republic of Uzbekistan Sh.M. Mirziyoyev states that "modern preschool education plays an important role in raising a healthy and mature generation." Currently, special attention is paid to preparing children for high-quality school education in preschool educational organizations under the jurisdiction of the Ministry of Preschool Education of the Republic of Uzbekistan. As a proof of this, in 2018, the coverage of children in the field of preschool education was 34.4%, and this indicator was 40.5% at the end of the half-year of 2019